Coumarin-diene photoswitches for rapid and efficient isomerization with visible light. Issue 39 (30th April 2018) - Richers, Matthew T.; Tran, Dinh Du; Wachtveitl, Josef; Ellis-Davies, Graham C. R.
Abstract : Coumarin-dienyl chromophores undergo rapid, fatigue-resistant bi-directional photoswitching with visible light. Abstract : We have developed 7-diethylaminocoumarin-based chromophores that photoisomerize with visible light. These photoswitches possess many desirable attributes, including large extinction coefficients (18 600–59 100 M −1 cm −1 ), high quantum yields (0.45–0.50) and resistance to photofatigue. Additionally, time-resolved spectroscopy indicates that both isomerization reactions are complete in less than 1 ns.